Synthesis method of core-shell structure cesium-lead halogen nanocrystal CsPbX3-coated ZnS
Through the synthesis method of core-shell structure cesium-lead halogen nanocrystal CsPbX3@ZnS, the problem of non-density coating on the surface of CsPbX3 nanocrystals is solved, and the high stability and good fluorescence performance of nanocrystals are achieved, which is suitable for luminescence. Diode material.
Patent Information
- Application Number
- CN202410907237.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2025-02-11
AI Technical Summary
The surface coating of existing CsPbX3 nanocrystals is not dense or durable, resulting in increased stability; or the luminescent performance is affected by dense inorganic coating.
The synthesis method of core-shell structure cesium-lead halogen nanocrystal CsPbX3@ZnS was used. By dissolving the CsPbX3 nanocrystal powder in octene, adding Zn(DDTC)2 and oleamine halogen OAmX, mixing ultrasonic and heating and cooling, then performing Centrifuge and dry to form ZnS-coated CsPbX3 nanocrystals.
The high stability and good fluorescence performance of CsPbX3 nanocrystals are achieved. The nanocrystals can be stored stably for 10 and 60 days in room temperature deionized water and air, and are suitable for light emitting diode materials.
Smart Images

Figure CN119410366A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing cesium-lead-halogen nanocrystals with a core-shell structure. Background Art
[0002] All-inorganic cesium lead halide CsPbX3 nanocrystals have excellent optical properties, adjustable band gap, high carrier mobility and photoluminescence quantum yield, and narrow luminescence half-peak width. The emission wavelength and band gap can be adjusted by adjusting the halogen atom X in CsPbX3, and can be used as the material for the light-emitting layer of cesium lead halide light-emitting diodes. However, the surface energy of CsPbX3 nanocrystals is relatively high, and the defect formation energy of halogen ion vacancies is the lowest, so halogen ion vacancy defects are most likely to occur on the surface of CsPbX3 nanocrystals. Surface defects are usually the initial sites for the decomposition of CsPbX3 NCs, and the defects not only cause non-radiative recombination of carriers, making it impossible for charges to flow freely, hindering the formation of current, causing the open circuit voltage to drop, and thus reducing the photoelectric conversion effect, but also promote the migration of halogen ions and causing the destruction of the crystal structure. The fundamental reason for the poor stability of the crystal structure of CsPbX3 nanocrystals is that the binding energy between ions is small and the halogen ions are easy to migrate. Therefore, changes in the polarity of the solution will cause changes and destruction in its crystal structure. When it comes into contact with polar solvents, especially water, it is easy to react and decompose. The chemical stability in water and humid air is poor, which can easily lead to a significant decrease in luminescence performance. The stability of the crystal structure of CsPbX3 nanocrystals in humid environments and even in air greatly hinders its promotion and application. Therefore, the use of surface coating technology to improve the stability of CsPbX3 nanocrystals has important theoretical value and engineering significance.
[0003] The use of organic or inorganic substances for surface coating can isolate CsPbX3 nanocrystals from the external environment and reduce the contact between nanocrystals and the external environment, thereby avoiding the destruction of the crystal structure of nanocrystals due to the polarity of the solution. Organic coating is mainly achieved by using low-density, flexible and stable organic polymers, such as epoxy resin and polystyrene, to coat cesium lead halide nanocrystals. Inorganic coating can be divided into dense inorganic shell and porous inorganic matrix according to composition and structure. The former forms a complete coating material such as SiO2, TiO2, silicate glass, etc. that forms a core-shell structure with the nanocrystal through reaction, while the latter uses partial coating materials such as mesoporous SiO2 and metal organic framework (MOF). At present, the surface coating of CsPbX3 nanocrystals has two problems: on the one hand, the surface coating is not dense or durable, resulting in the stability of CsPbX3 nanocrystals still needing to be improved; on the other hand, dense inorganic substances can completely coat nanocrystals, but the luminescence properties of CsPbX3 nanocrystals are affected. Summary of the invention
[0004] The present invention aims to solve the problem that the existing CsPbX3 nanocrystal surface coating is not dense or durable, resulting in the stability of the CsPbX3 nanocrystal to be improved; or there is a dense inorganic substance that can completely coat the nanocrystal, but the luminescence performance of the CsPbX3 nanocrystal is affected, and further provides a method for synthesizing core-shell structured cesium lead halide nanocrystals CsPbX3@ZnS.
[0005] A method for synthesizing core-shell structured cesium lead halogen nanocrystals CsPbX3@ZnS is carried out according to the following steps:
[0006] 1. Dissolve CsPbX3 nanocrystalline powder in octadecene, then add Zn(DDTC)2 and oleylamine halide OAmX, mix them evenly by ultrasonication, and obtain a mixture;
[0007] In the CsPbX3 nanocrystalline powder, X is one or a combination of two of I, Br and Cl;
[0008] 2. Heating the mixture at a temperature of 100°C to 140°C for 0.5h to 3h, and finally cooling to room temperature to obtain a crude solution of CsPbX3@ZnS nanocrystals;
[0009] 3. Centrifuge the crude solution of CsPbX3@ZnS nanocrystals and remove the supernatant to obtain a precipitate. Add a mixture of toluene and methyl acetate to the precipitate to dissolve it, then centrifuge and remove the supernatant, repeat the dissolution and centrifugation, and finally dry it to obtain core-shell structured cesium lead halide nanocrystals CsPbX3@ZnS.
[0010] The beneficial effects of the present invention are:
[0011] The preparation method of the present invention has the characteristics of low reaction temperature, short reaction time, etc., can reduce energy consumption, and has little environmental pollution. The final product of the present invention is ZnS-coated CsPbX3 nanocrystals (X is one or a combination of two of I, Br and Cl), which has high purity, an average particle size of about 12nm, a narrow particle size distribution, controllable size, good dispersibility, good crystal stability, and fluorescence performance is not affected by the coating layer. It can be stably stored in room temperature deionized water and air (temperature is 25°C, humidity is 40%) for 10 days and 60 days respectively, and is a material for preparing light-emitting diodes.
[0012] Instruction Manual
[0013] Figure 1 XRD spectra of the core-shell structured cesium lead halide nanocrystals CsPbX3@ZnS prepared in Examples 1 to 6;
[0014] Figure 2XRD spectra of the core-shell structured cesium lead halide nanocrystals CsPbBr3@ZnS prepared in Example 7 after being stored in deionized water at room temperature for 10 days and in air (temperature of 25° C., humidity of 40%) for 60 days;
[0015] Figure 3 TEM image of the core-shell structured cesium lead halide nanocrystal CsPbBr3@ZnS prepared in Example 7;
[0016] Figure 4 This is the EDX spectrum of each element of the core-shell structured cesium lead halide nanocrystal CsPbBr3@ZnS prepared in Example 7;
[0017] Figure 5 The fluorescence spectra of the core-shell structured cesium lead halide nanocrystals CsPbBr3@ZnS and CsPbBr3 nanocrystals prepared in Example 7;
[0018] Figure 6 The fluorescence intensity change curves of the core-shell structured cesium lead halide nanocrystals CsPbBr3@ZnS and CsPbBr3 nanocrystals prepared in Example 7 after being stored in air (temperature of 25°C and humidity of 40%) for different days. DETAILED DESCRIPTION
[0019] Specific implementation method 1: This implementation method is a method for synthesizing core-shell structured cesium lead halide nanocrystals CsPbX3@ZnS, which is carried out according to the following steps:
[0020] 1. Dissolve CsPbX3 nanocrystalline powder in octadecene, then add Zn(DDTC)2 and oleylamine halide OAmX, mix them evenly by ultrasonication, and obtain a mixture;
[0021] In the CsPbX3 nanocrystalline powder, X is one or a combination of two of I, Br and Cl;
[0022] 2. Heating the mixture at a temperature of 100°C to 140°C for 0.5h to 3h, and finally cooling to room temperature to obtain a crude solution of CsPbX3@ZnS nanocrystals;
[0023] 3. Centrifuge the crude solution of CsPbX3@ZnS nanocrystals and remove the supernatant to obtain a precipitate. Add a mixture of toluene and methyl acetate to the precipitate to dissolve it, then centrifuge and remove the supernatant, repeat the dissolution and centrifugation, and finally dry it to obtain core-shell structured cesium lead halide nanocrystals CsPbX3@ZnS.
[0024] The beneficial effects of this embodiment are:
[0025] The preparation method of this embodiment has the characteristics of low reaction temperature, short reaction time, etc., can reduce energy consumption, and has little environmental pollution. The final product of this embodiment is ZnS coated CsPbX3 nanocrystal (X is one or a combination of I, Br and Cl), which has high purity, an average particle size of about 12nm, a narrow particle size distribution, controllable size, good dispersibility, good crystal stability, and fluorescence performance is not affected by the coating layer. It can be stably stored in room temperature deionized water and air (temperature is 25°C, humidity is 40%) for 10 days and 60 days, respectively, and is a material for preparing light-emitting diodes.
[0026] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the Zn(DDTC)2 described in step 1 is zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate or zinc dibutyldithiocarbamate. The rest is the same as specific embodiment 1.
[0027] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the oleylamine halide OAmX in step 1 is one or a combination of oleylamine iodine, oleylamine bromide and oleylamine chloride. Other aspects are the same as specific embodiment 1 or 2.
[0028] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the volume ratio of the amount of CsPbX3 nanocrystalline powder to octadecene in step 1 is 1 mmol: (40-75) mL. Others are the same as specific embodiments 1 to 3.
[0029] Specific embodiment 5: This embodiment differs from Specific embodiments 1 to 4 in that the molar ratio of CsPbX3 nanocrystalline powder to Zn(DDTC)2 in step 1 is 1:(0.5-2). Other aspects are the same as Specific embodiments 1 to 4.
[0030] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the volume ratio of the amount of CsPbX3 nanocrystalline powder and oleylamine halide OAmX described in step 1 is 1 mmol: (0.2-0.65) mL. Others are the same as specific embodiments 1 to 5.
[0031] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that: in step 3, the CsPbX3@ZnS nanocrystal crude solution is centrifuged for 5 min to 20 min at a rotation speed of 6000 rpm to 10000 rpm, and then the supernatant is removed. The rest is the same as Specific embodiments 1 to 6.
[0032] Specific embodiment 8: This embodiment is different from specific embodiments 1 to 7 in that the volume ratio of the precipitate to the mixture of toluene and methyl acetate in step 3 is 1:(1-2). Other aspects are the same as specific embodiments 1 to 7.
[0033] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the volume ratio of toluene to methyl acetate in the mixture of toluene and methyl acetate described in step 3 is 1:(0.5-2). Others are the same as specific embodiments 1 to 8.
[0034] Specific embodiment 10: This embodiment differs from Specific embodiments 1 to 9 in that: in step 3, a mixture of toluene and methyl acetate is added to the precipitate to dissolve it, and then centrifuged for 5 to 20 minutes at a rotation speed of 5000 rpm to 8000 rpm, and the supernatant is removed, and the dissolution and centrifugation are repeated 2 to 3 times. The rest is the same as Specific embodiments 1 to 9.
[0035] The following examples are used to verify the beneficial effects of the present invention:
[0036] Embodiment 1:
[0037] A method for synthesizing core-shell structured cesium lead halogen nanocrystals CsPbX3@ZnS is carried out according to the following steps:
[0038] 1. Dissolve CsPbBr3 nanocrystalline powder in octadecene, then add Zn(DDTC)2 and oleylamine halide OAmX, mix them evenly by ultrasonication, and obtain a mixture;
[0039] The volume ratio of the amount of CsPbBr3 nanocrystalline powder to octadecene is 1mmol:60mL;
[0040] The molar ratio of the CsPbBr3 nanocrystalline powder to Zn(DDTC)2 is 1:1.5;
[0041] The volume ratio of the amount of the CsPbBr3 nanocrystalline powder to the oleylamine halide OAmX is 1mmol:0.4mL;
[0042] The Zn(DDTC)2 is zinc diethyldithiocarbamate;
[0043] The oleylamine halide OAmX is oleylamine bromide;
[0044] 2. The mixture was heated at 120°C for 1 hour and finally cooled to room temperature to obtain a crude solution of CsPbBr3@ZnS nanocrystals;
[0045] 3. Centrifuge the crude solution of CsPbBr3@ZnS nanocrystals for 10 min at a rotation speed of 10000 rpm, remove the supernatant to obtain a precipitate, add a mixture of toluene and methyl acetate to the precipitate to dissolve it, then centrifuge it for 5 min at a rotation speed of 7000 rpm, remove the supernatant, repeat the dissolution and centrifugation for 2 times, and finally dry it to obtain core-shell structure cesium lead halide nanocrystals CsPbBr3@ZnS, i.e. CsPbBr3@ZnS-1;
[0046] The volume ratio of the precipitate to the mixture of toluene and methyl acetate is 1:1;
[0047] The volume ratio of toluene to methyl acetate in the mixture of toluene and methyl acetate is 1:1.
[0048] Example 2: This example is different from Example 1 in that: in step 1, CsPbClBr2 nanocrystalline powder is dissolved in octadecene; the oleylamine halide OAmX in step 1 is a mixture of oleylamine chloride and oleylamine bromide in a molar ratio of 1:2; and in step 3, core-shell structured cesium lead halide nanocrystalline CsPbClBr2@ZnS, i.e., CsPbClBr2@ZnS-1, is obtained. The rest is the same as in Example 1.
[0049] Embodiment 3: This embodiment is different from Embodiment 1 in that: in step 1, CsPbCl2Br nanocrystalline powder is dissolved in octadecene; the oleylamine halide OAmX in step 1 is a mixture of oleylamine chloride and oleylamine bromide in a molar ratio of 2:1; and in step 3, core-shell structured cesium lead halide nanocrystalline CsPbCl2Br@ZnS, i.e., CsPbCl2Br@ZnS-1, is obtained. The rest is the same as in Embodiment 1.
[0050] Embodiment 4: This embodiment is different from Embodiment 1 in that: in step 1, CsPbCl3 nanocrystalline powder is dissolved in octadecene; the oleylamine halide OAmX in step 1 is oleylamine chloride; and in step 3, core-shell structured cesium lead halide nanocrystalline CsPbCl3@ZnS, i.e., CsPbCl3@ZnS-1, is obtained. The rest is the same as in Embodiment 1.
[0051] Embodiment 5: This embodiment is different from Embodiment 1 in that: in step 1, CsPbClBr2 nanocrystalline powder is dissolved in octadecene; the oleylamine halide OAmX in step 1 is a mixture of oleylamine chloride and oleylamine bromide in a molar ratio of 1:2; in step 2, the mixture is heated at 140°C for 1h, and finally cooled to room temperature to obtain a CsPbClBr2@ZnS nanocrystalline crude solution; in step 3, core-shell structured cesium lead halide nanocrystalline CsPbClBr2@ZnS, i.e., CsPbClBr2@ZnS-2, is obtained. The rest is the same as in Embodiment 1.
[0052] Example 6: This example is different from Example 1 in that: in step 1, CsPbCl2Br nanocrystalline powder is dissolved in octadecene; the oleylamine halide OAmX in step 1 is a mixture of oleylamine chloride and oleylamine bromide in a molar ratio of 2:1; in step 2, the mixture is heated at 140°C for 1h, and finally cooled to room temperature to obtain a CsPbCl2Br@ZnS nanocrystalline crude solution; in step 3, core-shell structured cesium lead halide nanocrystalline CsPbCl2Br@ZnS, i.e., CsPbCl2Br@ZnS-2, is obtained. The rest is the same as in Example 1.
[0053] Embodiment seven:
[0054] A method for synthesizing core-shell structured cesium lead halogen nanocrystals CsPbX3@ZnS is carried out according to the following steps:
[0055] 1. Dissolve CsPbBr3 nanocrystalline powder in octadecene, then add Zn(DDTC)2 and oleylamine halide OAmX, mix them evenly by ultrasonication, and obtain a mixture;
[0056] The volume ratio of the amount of CsPbBr3 nanocrystalline powder to octadecene is 1mmol:60mL;
[0057] The molar ratio of the CsPbBr3 nanocrystalline powder to Zn(DDTC)2 is 1:1;
[0058] The volume ratio of the amount of the CsPbBr3 nanocrystalline powder to the oleylamine halide OAmX is 1mmol:0.4mL;
[0059] The Zn(DDTC)2 is zinc dimethyldithiocarbamate;
[0060] The oleylamine halide OAmX is oleylamine bromide;
[0061] 2. The mixture was heated at 110°C for 1 hour and finally cooled to room temperature to obtain a crude solution of CsPbBr3@ZnS nanocrystals;
[0062] 3. Centrifuge the crude solution of CsPbBr3@ZnS nanocrystals for 10 min at a rotation speed of 10000 rpm, remove the supernatant to obtain a precipitate, add a mixture of toluene and methyl acetate to the precipitate to dissolve it, then centrifuge it for 5 min at a rotation speed of 7000 rpm, remove the supernatant, repeat the dissolution and centrifugation for 2 times, and finally dry it to obtain core-shell structure cesium lead halide nanocrystals CsPbBr3@ZnS, i.e. CsPbBr3@ZnS;
[0063] The volume ratio of the precipitate to the mixture of toluene and methyl acetate is 1:1.5;
[0064] The volume ratio of toluene to methyl acetate in the mixture of toluene and methyl acetate is 1:1.
[0065] Figure 1 The XRD spectra of the core-shell structure cesium lead halide nanocrystals CsPbX3@ZnS prepared in Examples 1 to 6 are shown in the figure. As can be seen from the figure, the diffraction peaks of the obtained materials are relatively high and sharp, and the characteristic peaks are all the characteristic peaks of ZnS, indicating that the ZnS coated on the surface of the nanocrystals is dense and complete, and has strong crystallinity; there is no obvious impurity peak, indicating that the obtained nanocrystals are pure phase. It can be seen that the method can be used to prepare core-shell structure cesium lead halide nanocrystals CsPbX3@ZnS nanocrystals with good crystallinity.
[0066] Figure 2 The XRD spectra of the core-shell structured cesium lead halogen nanocrystal CsPbBr3@ZnS prepared in Example 7 after being stored in deionized water at room temperature for 10 days and in air (temperature of 25°C, humidity of 40%) for 60 days; as can be seen from the figure, the XRD spectra of the nanocrystals after being stored in water for 10 days and in air for 60 days do not change. This indicates that the core-shell structured cesium lead halogen nanocrystal CsPbBr3@ZnS can be stably stored in water for 10 days and in air for 60 days.
[0067] Figure 3 This is a TEM image of the core-shell structured cesium lead halide nanocrystal CsPbBr3@ZnS prepared in Example 7. As can be seen from the figure, it exhibits a typical cubic shape with a uniform particle size of about 12 nm. The ZnS shell is relatively thin and difficult to identify.
[0068] Figure 4 The EDX spectrum of each element of the core-shell structured cesium lead halide nanocrystal CsPbBr3@ZnS prepared in Example 7; Since the electron density contrast of the ZnS shell is low, it is difficult to identify in the TEM image with image contrast, so the TEM energy dispersive X-ray (EDX) spectrum of CsPbBr3@ZnS is measured. As can be seen from the figure, a clear core-shell boundary line can be clearly observed in the figure - high content of Zn and S elements are found at both ends of the shell, and high content of Cs, Pb and Br elements are found in the core. This proves the formation of the CsPbBr3@ZnS core-shell structure.
[0069] Figure 5The fluorescence spectra of the core-shell structured cesium lead halide nanocrystals CsPbBr3@ZnS and CsPbBr3 nanocrystals prepared in Example 7 are shown in the figure. Compared with the nanocrystal CsPbBr3, the fluorescence spectrum of the core-shell structured nanocrystal CsPbBr3@ZnS has a slight blue shift of about 5nm, but the fluorescence intensity has not changed. This shows that due to the coating of the nanocrystal CsPbBr3 with ZnS, the photon energy of the photoluminescence is slightly increased, but its optical properties are not affected.
[0070] Figure 6 The fluorescence intensity change curves of the core-shell structure cesium lead halide nanocrystals CsPbBr3@ZnS and CsPbBr3 nanocrystals prepared in Example 7 after being stored in air (temperature 25°C, humidity 40%) for different days. As can be seen from the figure, as the storage time increases, the photoluminescence intensity of the nanocrystal CsPbBr3 decreases rapidly, and drops to 14% of the original intensity after 7 days; while the photoluminescence intensity of the core-shell structure nanocrystals CsPbBr3@ZnS can still maintain 85% of the original intensity after being stored in air for 60 days.
Claims
1. A method for synthesizing core-shell structured cesium lead halide nanocrystals CsPbX3@ZnS, characterized in that It is carried out in the following steps:
1. Dissolve CsPbX3 nanocrystalline powder in octadecene, then add Zn(DDTC)2 and oleylamine halide OAmX, mix them evenly by ultrasonication, and obtain a mixture; In the CsPbX3 nanocrystalline powder, X is one or a combination of two of I, Br and Cl; 2. Heating the mixture at a temperature of 100°C to 140°C for 0.5h to 3h, and finally cooling to room temperature to obtain a crude solution of CsPbX3@ZnS nanocrystals; 3. Centrifuge the crude solution of CsPbX3@ZnS nanocrystals and remove the supernatant to obtain a precipitate. Add a mixture of toluene and methyl acetate to the precipitate to dissolve it, then centrifuge and remove the supernatant, repeat the dissolution and centrifugation, and finally dry it to obtain core-shell structured cesium lead halide nanocrystals CsPbX3@ZnS.
2. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that The Zn(DDTC)2 described in step 1 is zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate or zinc dibutyldithiocarbamate.
3. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that The oleylamine halide OAmX in step 1 is one of oleylamine iodine, oleylamine bromide and oleylamine chloride, or a combination of several thereof.
4. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that The volume ratio of the amount of CsPbX3 nanocrystalline powder described in step 1 to octadecene is 1 mmol: (40-75) mL.
5. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that The molar ratio of the CsPbX3 nanocrystalline powder to Zn(DDTC)2 described in step 1 is 1:(0.5-2).
6. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that The volume ratio of the amount of CsPbX3 nanocrystalline powder described in step 1 to the oleylamine halide OAmX is 1 mmol: (0.2-0.65) mL.
7. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that In step 3, the crude CsPbX3@ZnS nanocrystal solution is centrifuged at a rotation speed of 6000 rpm to 10000 rpm for 5 min to 20 min, and then the supernatant is removed.
8. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that The volume ratio of the precipitate described in step 3 to the mixture of toluene and methyl acetate is 1:(1-2).
9. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 8, characterized in that The volume ratio of toluene to methyl acetate in the mixture of toluene and methyl acetate described in step 3 is 1:(0.5-2).
10. The method for synthesizing a core-shell structured cesium lead halide nanocrystal CsPbX3@ZnS according to claim 1, characterized in that In step 3, a mixture of toluene and methyl acetate is added to the precipitate to dissolve it, and then centrifuged at a speed of 5000 rpm to 8000 rpm for 5 min to 20 min, and the supernatant is removed, and the dissolution and centrifugation are repeated 2 to 3 times.